The Experience of Genetic Counselors Working with Patients Facing the Decision of Pregnancy Termination after 24 Weeks Gestation. Issue 3 (27th September 2017) - Graziani, Rachel N. A.; Nemzer, Laurie; Kerns, Jennifer
Abstract: Prenatal genetic counselors are health care professionals who counsel women making reproductive decisions which include decisions such as terminating pregnancies due to fetal anomalies. Little is known about the experiences and practices of prenatal genetic counselors working with women who have the option of termination after 24 weeks gestation. In this national survey of 168 genetic counselors who have practiced prenatal genetic counseling, we asked about their general practice patterns, including indications for which termination is offered and types of abortion care services that are coordinated by genetic counselors. We report respondents' self‐assessments of level of understanding of federal abortion law and abortion procedures. Seventy‐six percent of respondents have offered and counseled on termination after 24 weeks and 93% of respondents believe it is the responsibility of the counselor to discuss this option with patients. However, one‐third report that they have some or no understanding of the procedures and three‐quarters report that they have some or no understanding of federal abortion law. The results of this study provide insight into knowledge and experiences of genetic counselors working with these patients, allowing for improved genetic counselor training and continuing education to provide better guidance and develop more effective means of assisting patients.